مداخل التحسين المستمر: دراسة مقارنة (Journal of Accounting and Financial Studies ( JAFS ), 2009)
Continuous improvement, or Kaizen, is a philosophy that is based on the idea of continuously finding ways to improve things.  From this point of view, continuous improvement is not limited to the quality of products or services but it also applies to all the processes in the organization.  During the last two decades several continuous improvement approaches were developed and marketed.  The advocates of each approach claim that their approach is the best, however all the approaches had their own advantages and disadvantages and had their share of criticism.  The important question is how to choose the right continuous improvement approach?  This research work addresses the philosophy, the concepts, the assumptions, and the domain of each approach and compares them thoroughly.  In addition, we present a theoretical framework to assist the organization in choosing one of the continuous improvement approaches that corresponds to the organization's culture and quality problems.